Left atrial appendage thrombosis in a patient with Friedreich Ataxia–related cardiomyopathy, left ventricular systolic dysfunction, and atrial fibrillation. (October 2021) - Russo, Michele; Nuzzo, Annachiara; Foschi, Matteo; Boarin, Simona; Lorenzetti, Stefano; Tomasi, Corrado; Querzani, Pietro; Rubboli, Andrea
Friedreich ataxia is the most common form of hereditary ataxia. Heart involvement in Friedreich ataxia is common and can include increased left ventricular wall thickness, atrial fibrillation, and in the later stages, a reduction of left ventricular ejection fraction. We present the case of a 45-year-old man with a history of paroxysmal atrial fibrillation and a congestive heart failure, hypertension, age ⩾ 75 years, diabetes mellitus, stroke, vascular disease, age 65–74 years, and female sex (CHA2DS2-VASc) score of only 1 (because of reduced left ventricular ejection fraction) who presented with pneumonia and was also found to have atrial fibrillation with a rapid ventricular response. Despite already being on long-term therapy with a non-vitamin K-antagonist oral anticoagulant, a transesophageal echocardiogram showed a mobile floating thrombus in the left atrial appendage. In accordance with previous necropsy evidence of thrombosis and thromboembolism in Friedreich ataxia subjects who likely have had only non-sex-related CHA2DS2-VASc score ⩽1, this case suggests that the risk of thromboembolism in Friedreich ataxia subjects with atrial fibrillation may not be adequately predicted by the sole CHA2DS2-VASc score.